Air breakdown under lightning impulse with plane-plane electrode - Ab. Hadi, Nik Aznan (2014)
Breakdown voltage is a phenomenon where the quantity of an electrical force is required to transform the electrical properties of an object. In other words, breakdown voltage is also called the striking voltage. This breakdown voltage of an insulator is the minimum voltage that can cause some part of the insulator to become electrically conductive. The high voltage power equipment is mainly subjected to spark over voltage. Spark over can be useful in some cases (for example spark plug ) and may give side effect or damage (sparking in switching devices) to machine. Therefore the research about the behavior of spark over and breakdown voltage is significant in electrical engineering designing process. The project is started with experimental setup to get the standard impulse voltage. This lightning impulse voltage is ensured to follow the standard of BS EN 60060-1:2010. The procedure of this experiment follows the TERCO catalogue documentation. In this project, the standard plane to plane gap is used to measure the peak value of DC impulse voltages. The gap length between the planes will be varied. Lightning-impulse voltage is an impulse voltage with a front time less than 20μs. In this project, the FEMM software is used for modeling and analysis of electric field distribution in plane to plane electrode. This software provides a wide range of simulation applications for controlling the complexity of both modeling and analysis of a system. The electrodes gap distances are being varied to 5 different gaps which are 10 mm, 15 mm, 20 mm, 25 mm and 30 mm. The simulation of electric field was done for plane to plane electrode arrangement with 5 different gaps and the result of analyzing using FEMM will be discussed here.